PENGARUH SISTEM KEPERCAYAAN DALAM KEHIDUPAN MASYARAKAT BATAK TOBA TERHADAP RAGAM HIAS PADA ARSITEKTURNYA - Ganal Rudiyanto (Jurnal Dimensi Seni Rupa dan Desain, 2003)
Abstract: In the simple way, it could be expressed that the aim of this script are mainly to prove by quoting the realtionship or effects in the Batak Toba Community lives towards the shape & miscellaneous a scressaories in the architectural view. In the implementation by explicitting the concepts clearly which are still seen implisit. Form each meaning of communities simbolic believes and the miscellaneous accessories in their Batak Toba culture house, by inventoring their believing system structuring their familty trees until the usage of the symbols